Nova proposição para verificação do estado-limite de flambagem lateral com distorção de vigas mistas de aço e concreto - Janaina Pena Soares de Oliveira (2018)
In the internal supports, the continuous composite steel-concrete beams are subject to hogging moment, hence, the bottom and part of the web of the steel member is in compression. If the web of the steel profile does not have enough stiffness to avoid the lateral bending, the web willdistort allowing the compressed flange to displace laterally and twist, characterizing buckling mode known as lateral distortion buckling (LDB). The method to verify the LDB of the European code EN 1994-1-1:2004 originated the Brazilian standard ABNT NBR 8800:2008 prescription. The main difference between them is in the fact that EN 1994-1-1:2004 does not provide expression for the calculation of elastic critical moment, while ABNT NBR 8800:2008 prescribes a formulation proposed by researches in the 1990s. The equations present in the literature for the determination of elastic critical moment present a lot of inconsistencies. For this reason, a parametric study is proposed for the determination of a new equation for the calculation of the elastic critical moment of continuous composite steel-concrete beams. For this, elastic buckling analysis were performed using the software Ansys 17.0 (2016) in finite element models that describe the behavior of continuous composite steel-concrete beams. The numeric models were composed by steel profile, rotational spring and lateral restraint, both applied along the beam span to restrain the steel top flange. Furthermore, to evaluate the methods of calculation of European and Brazilian standards to obtained the nominal hoggingmoment of LDB, in this thesis were implemented inelastic numerical models in finite elements, using the software Ansys 17.0 (2016), considering the inverted U-mechanism and taking into account the geometric and material imperfections (residual stresses) and the cracking of concrete. The influence of adjacent span at the analyzed span also was verified. For this, the numerical models have two span and three supports to represent the end span and three spans with four supports to simulate the internal spans. As a result, the calculation methods prescribed by the mentioned standards were evaluated. Also, a simplified equation for the determination of the slenderness and the new equation of reduction factor for the LDB were proposed